Academic Resilience as a Foundation for Superior Human Capital: A Narrative Study of Final-Year Students - Mercidominick Fidelius Conrad Menachem Purba (CV Projurnal Mitra Publikasi, 2025)
Final-year university students frequently experience intense academic pressure arising from thesis completion, time constraints, and limited institutional support, which may negatively affect their psychological well-being academic performance. Academic resilience plays a crucial role in enabling students to adapt to these challenges and prepare for professional life. This study aims to explore the lived experiences of final-year students in dealing with academic pressure and to identify coping strategies that contribute to the development of academic resilience as a foundation for superior human capital. This research employed a qualitative narrative approach involving one final-year student selected through purposive sampling. Data were collected through semi-structure online interviews lasting 15-30 minutes and analysed using narrative thematic analysis, including transcription, repeated reading, and inductive theme development. Data credibility was ensured through member checking and triangulation. The findings indicate that the participant experienced significant academic pressure related to workload, time management, lecturer expectations, and limited internship opportunities. To cope with these challenges, the participant applied adaptive strategies such as positive distraction, peer support, and internalization of academic responsibility. These strategies strengthen self-discipline, persistence, and emotional regulation. The study demonstrates that academic resilience is essential in helping final-year students manage academic stress and develop professional readiness. By fostering adaptive coping strategies, students can enhance their autonomy, consistency, and work ethics. Therefore, higher education institutions are encouraged to strengthen academic support systems and counselling service to promote student resilience and sustainable human capital development.